Metric regularity of composition set-valued mappings: metric setting and coderivative conditions - Marius Durea; VanNgai Huynh; Huu Tron Nguyen; Radu Strugariu (My University, 2014)
Metric regularity of composition set-valued mappings: metric setting and coderivative conditions
Keywords: Composition mappings; Coderivative conditions; Metric setting